The association of maternal-fetal attachment with smoking and smoking cessation during pregnancy in The FinnBrain Birth Cohort Study - Heidi Jussila; Juho Pelto; Riikka Korja; Eeva Ekholm; Marjukka Pajulo; Linnea Karlsson; Hasse Karlsson (BMC, 2020)
Abstract Background Smoking in pregnancy constitutes a preventable risk factor for fetal/child development and maternal-fetal attachment (MFA) seems to contain a momentum that can break the chain of adverse outcomes by promoting maternal prenatal health practices. This study aimed to explore the association of MFA with smoking at any time during pregnancy and smoking cessation in early pregnancy, and the modifying role of MFA on the expected effects of education and prenatal psychological distress (PPD) on prenatal smoking behavior. Methods The pregnant women (n = 3766) participated in the The FinnBrain Birth Cohort Study in Finland between December 2011 and April 2015. The binary outcomes, smoking at any time during pregnancy and smoking cessation in early pregnancy, were obtained from self-reports at gestational weeks (gwks) 14 and 34 and The Finnish Medical Birth Register. MFA was assessed with the Maternal-Fetal Attachment Scale (MFAS) at gwks 24 and 34. Logistic regression analyses were used to determine the association between MFA and maternal prenatal smoking behavior. Findings The prevalence of smoking was 16.5%, and 58.1% of the smokers quit smoking during pregnancy. The independent associations of total MFA scores with prenatal smoking behavior were not established (aOR = 1.00-1.02, multiplicity adjusted p > 0.05). A higher score in the altruistic subscale of MFA, Giving of self, associated with a higher probability of smoking cessation (24 gwks: aOR = 1.13, 95% CI [1.04, 1.24], p = 0.007, multiplicity adjusted p = 0.062; 34 gwks: aOR = 1.17, 95% CI [1.07, 1.29], p < 0.001, multiplicity adjusted p = 0.008). The modifying effect of MFA on the observed associations between PPD and smoking in pregnancy and between maternal education and smoking in pregnancy / smoking cessation in early pregnancy was not demonstrated. Conclusions The altruistic dimension of maternal-fetal attachment associates with an increased probability of smoking cessation during pregnancy and therefore strengthening altruistic maternal-fetal attachment may constitute a promising novel approach for interventions aiming at promoting smoking cessation during pregnancy.